(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Beta-thalassemia, an autosomal recessive hemoglobinopathy, affects over 80 million carriers globally, with high prevalence in the "thalassemia belt" spanning from the Mediterranean to Southeast Asia [1]. Uzbekistan, located in Central Asia, faces significant challenges due to the absence of systematic screening programs, leading to underreported cases and delayed medical interventions [5]. Approximately 30% of rural marriages in Uzbekistan are consanguineous, amplifying the transmission of recessive genetic disorders [2]. Diagnostic delays are common, with a median age at diagnosis of 2.8 years, resulting in irreversible complications such as iron overload [5]. Furthermore, access to essential treatments like deferasirox, a first-line iron chelator, remains limited, with only 18% of patients receiving it.